Complete diphallia associated with unusual multiple congenital anomalies: case report and review of literatures - Bassam Khaleel Al-Abbasi (SpringerOpen, 2022)
Abstract Background Diphallus (duplication of phallus) is rarely encountered in surgical practice with only 100 cases reported in literature. Some cases may be isolated but mostly associated with other anomalies, without clear data about its etiology. Case presentation We reported a 1-day-old newborn baby who was presented with complete duplication of the phallus, one of them being hypospadic associated with a high type imperforate anus, omphalocele, congenital pouch colon, sacral meningocele, and other congenital anomalies not reported before in such combinations. Multiple stages surgical corrective procedures were performed over a period of 4 years with 4-6 months interval between each stage, starting with the management of omphalocele and colostomy, ended by excision of the abnormal phallus with abdominoplasty and closure of colostomy. The outcome was evaluated, and literatures were reviewed in relation to types, presentations, and options for surgical correction with optimal outcomes. Conclusion A combination of diphallia and other abnormalities in our patient are not reported previously in such manner and were very difficult to be corrected. Only expert pediatric surgeons should treat such conditions as every case is unique in nature. In all conditions, the abnormal phallus should be excised, and the final aim is to achieve a continent child with cosmetically acceptable genitalia.